2021
DOI: 10.1002/ece3.7784
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in the size of Chinese lizards are driven by multiple factors

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 50 publications
2
25
0
1
Order By: Relevance
“…Expressly, our results found evidence for the influence of both resource availability and seasonality (i.e., precipitation seasonality) on female body size, with smaller body sizes associated with decreased seasonality and lower primary productivity. Previous studies have suggested that highly seasonal changes in rainfall significantly influence the abundance of available resources for female lizards (Valenzuela-Sanchez et al, 2015;Meiri et al, 2020;Slavenko et al, 2021), which is positively related to large body sizes (Liang et al, 2021). Perhaps this is not surprising since unpredictable seasonal changes at high altitudes may suggest scarce resources for lizards (Deme et al, 2022a;Anderson et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Expressly, our results found evidence for the influence of both resource availability and seasonality (i.e., precipitation seasonality) on female body size, with smaller body sizes associated with decreased seasonality and lower primary productivity. Previous studies have suggested that highly seasonal changes in rainfall significantly influence the abundance of available resources for female lizards (Valenzuela-Sanchez et al, 2015;Meiri et al, 2020;Slavenko et al, 2021), which is positively related to large body sizes (Liang et al, 2021). Perhaps this is not surprising since unpredictable seasonal changes at high altitudes may suggest scarce resources for lizards (Deme et al, 2022a;Anderson et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast studies have shown some ectotherms follow Bergmann's rule, possessing large body sizes at high latitudes (e.g., Angilletta et al, 2004). The original explanation for Bergman's rule did not account for the peculiarity of ectotherms (Watt et al, 2010) in their inability to generate significant internal body heat, and consequently that a larger bodied ectotherm would therefore heat up more slowly (Stevenson, 1985) and would lack the ability to conserve heat in colder environments (Liang et al, 2021). Further, possessing larger bodies in colder environments may be deleterious to some ectotherm species (Jadin et al, 2019;Velasco et al, 2020;Slavenko et al, 2021); since ectotherms with large body sizes that slowly heat up in colder environments show constrained thermoregulatory behavior (Pincheira-Donoso et al, 2008;Anderson et al, 2022;Szymkowiak and Schmidt, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations